Adult pilomyxoid astrocytoma with hemorrhage in an atypical location - Karthigeyan, Madhivanan; Singhal, Prankul; Salunke, Pravin; Vasishta, Rakesh (Asian Journal of Neurosurgery, 2019)
Pilomyxoid astrocytomas (PMAs) are generally seen in young children and tend to occur in the hypothalamic–chiasmatic region. Their presence in other parts of the brain in the nonpediatric age group is uncommon. In addition, hemorrhage in such low-grade tumors is an occasional event. We describe a case of PMA that presented with spontaneous bleed in an atypical location (temporoparietal region) in an adult. A concise literature of the cases of PMA which were associated with bleed is also presented. Occasionally, low-grade tumors such as PMA may present with bleed. These benign looking neoplasms behave differently from the commonly occurring pilocytic astrocytomas (PAs) and should be considered as a differential. It is important to differentiate these from PA, as the management and prognosis differs.
Keywords: Astrocytoma; hemorrhage; intratumoral; pilocytic; pilomyxoid; tumor